How Does Industrial Structure Upgrading Affect the Global Greenhouse Effect? Evidence From RCEP and Non-RCEP Countries - Dong, Jiajia; Dou, Yue; Jiang, Qingzhe; Zhao, Jun (Frontiers in Energy Research, 2021)
This study empirically investigates the impact of industrial structure upgrading on global carbon dioxide (CO2) emissions by employing a balanced dataset of 73 countries over the period 1990-2019. After conducting a series of empirical tests, we use the fixed effect (FE) and random effect (RE) methods to estimate the econometric model, and divide the full sample data into two subsamples, i.e., regional comprehensive economic partnership (RCEP) countries and non-RCEP countries, for heterogeneous analysis. This paper also examines the mediating role of technological innovation in the relationship between industrial structure upgrading and global CO2 emissions. The main findings indicate that: (1) both industrial structure upgrading and technological innovation show significant negative impacts on CO2 emissions in the global panel, the RCEP countries, and the non-RCEP countries; (2) industrial structure upgrading not only affects CO2 emissions directly, but also has an indirect impact on global CO2 emissions by promoting technological innovation; and (3) the environmental Kuznets curve (EKC) hypothesis is verified in this study; in other words, both economic growth and CO2 emissions exhibit a significant inverted U-shaped relationship in the global panel, the RCEP countries, and the non-RCEP countries. Finally, we highlight some important policy implications with respect to promoting industrial structure upgrading and mitigating the greenhouse effect.